2012
DOI: 10.1101/cshperspect.a006643
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs as Modulators of Angiogenesis

Abstract: MicroRNAs are highly expressed in endothelial cells, and recent data suggest that they regulate aspects of vascular development and angiogenesis. This study highlights the state of the art in this field and potential therapeutic opportunities. MicroRNAs (miRNAs) represent a family of conserved short (22 nt) noncoding single-stranded RNAs that have been identified in plants and animals. They are generated by the sequential processing of the RNA template by the enzymes Drosha and Dicer, and mature miRNAs can reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 86 publications
(133 reference statements)
1
118
1
Order By: Relevance
“…Previous studies have identified the miR-17/92 cluster, let-7 family and miR-145 as the modulators of angiogenesis [41]. The validated targets of the miR-17/92 cluster include TSP-1, CTGF, TIMP-1 and ITG5a.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified the miR-17/92 cluster, let-7 family and miR-145 as the modulators of angiogenesis [41]. The validated targets of the miR-17/92 cluster include TSP-1, CTGF, TIMP-1 and ITG5a.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [98] demonstrated that melatonin suppresses tumor angiogenesis by inhibiting HIF-1 and VEGF via sphingosine kinase 1 in colon cancer cells. On the other hand, miRNAs play critical roles as modulators of angiogenesis [99]; e.g., overexpression of miRNA 3195 and miRNA 374b inhibits mRNA expression of HIF-1alpha, HIF-2alpha, and VEGF in hypoxia in prostate cancer cells, melatonin enhancing the expression of these miRNAs [100]. Therefore, the anti-angiogenic activity of melatonin can be the result of suppressing of HIF-1alpha by miRNA.…”
Section: Anti-angiogenic Activitymentioning
confidence: 99%
“…Indeed, it has been proposed that EC death is one of the critical determinants of radiation damage34, a key therapeutic modality in cancer treatment. Since miRs influence several aspects of endothelial function5, we hypothesized that miRs regulate endothelial apoptosis in response to radiation damage. We have identified a microRNA (miR) signature in ECs induced in common by genotoxic stress, oxidative stress and DNA damage.…”
mentioning
confidence: 99%